Which of the following tests aspartate aminotransferase, alanine transaminase and alkaline phosphatase, can predict poor outcomes in Coronavirus 2019 patients? a retrospective cohort study - Pouyan Ebrahimi; AmirHossein Nasiri-Valikboni; Mahmoud Sadeghi Haddad Zavareh; Hoda Shirafkan; Seyed Hassan Abedi (Journal of Kerman University of Medical Sciences)
Background:Coronavirus 2019 (COVID-19) disease caused a recent pandemic that killed thousands of people by causing mild and severe systemic organ involvement. Researchers are still trying to find the proper diagnosis tool for the disease. In addition, we investigated the effect of aspartate aminotransferase (AST), alanine transaminase (ALT), and alkaline phosphatase (ALP) enzymes on long-term outcomes.Methods:The variables in this retrospective cohort study were collected from the records of patients with Covid-19 referred to Rouhani Hospital in Mazandaran, northern Iran. Patients were followed up to the cut-off points for mortality.Results:Among 320 eligible patients, AST levels, unlike ALT and ALP, were significantly associated with mortality (p<0.001) and disease severity (p=0.016). The level of AST, unlike the level of other tests examined at the time of referral, has a significant effect on mortality at admission time (p < 0.001, 95% CI= 2.433 to 20.463, MD = 7.056) and time of admission to the intensive care unit (ICU) (P = 0.012, 95% CI= 1.291 to 7.907, MD = 3.195). None of the tests (AST, ALT and ALP) could predict long-term mortality in patients.Conclusions:AST levels, unlike ALP and ALT levels, have shown an excellent ability to predict mortality and severity at admission, but neither of AST, ALT and ALP predicted long-term adverse outcomes.